Podnikatelský záměr - Hnátek, Robert (Vysoké učení technické v Brně. Fakulta podnikatelská, 2012)
Diplomová práce „Podnikatelský záměr“ se zabývá hodnocením současné situace vybraného podniku. Na základě jednotlivých analýz je vypracován podnikatelský záměr pro uvedení nových produktů zahraničního výrobce na český trh. Diplomová práce se skládá z teoretické části, z analýzy problémů a z návrhu vlastního řešení.

This Master’s thesis "Business plan" deals with evaluation of the current situation of the selected company. On the based of various analyzes is prepared a business plan for the introduction of new products of foreign producers on the Czech market. This thesis consists of theoretical part, the analysis of problems and proposal of own solution.
Business Plan
Keywords: Podnikatelský záměr; SWOT analýza; PEST analýza; marketingový mix; Porterův model konkurenčního prostředí; finanční analýza; likvidita; rentabilita; účetní výkazy.; Business plan; SWOT analysis; PEST analysis; marketing mix; Porter’s model of competitive environment; financial anlalysis; liquidity; profitability; accounting statements.